EEG Epileptiform Discharges in "Healthy" Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers from Helios Klinikum Wuppertal, Germany, analyzed the prevalence of epileptiform discharges in digitally recorded EEG (DEEG) of 382 healthy children (226 male, 156 female) ages 6-13 years, and compared the data to those of previously published paper analog recordings.